Histopathological correlates of sinoatrial disease. - Demoulin, J C (1978)
Six hearts from patients suffering from rhythm disorders consistent with the diagnosis of sinoatrial disease were histologically examined. Four of the patients had shown a tachycardia-bradycardia syndrome, and the remaining two patients episodes of sinus arrest or sinoatrial block with a slow junctional escape rhythm. The rhythm disorders had occurred in the setting of chronic sinoatrial disease (3 cases), acute myocardial infarction (2 cases), and diphtheritic myocarditis (1 case). The abnormalities which were more consistently observed consisted of (1) total or subtotal destruction of the sinus node (6 cases); (2) total or subtotal destruction of the areas of nodal atrial continuity (5 cases); (3) inflammatory or degenerative changes of the nerves and ganglia surrounding the node (6 cases); (4) pathological changes in the atrial wall (5 cases). Chronic or acute lesions involving the AV node, the bundle of His, and its branches or their distal subdivisions were also found in all 6 hearts. The relationship between the observed pathological changes and the physiological disorders are discussed.